INNOVATIVE TECHNOLOGIES IN EDUCATION - Dilshodakhon Muminova (Bright Mind Publishing, 2025)
The modern education system is increasingly competing with the entertainment sector, necessitating new methods to actively engage students in learning. Given the rapid advancement of Virtual Reality (VR) and Augmented Reality (AR) technologies, it is essential to incorporate educational content, particularly school subjects, into application development. This approach aims to create an optimal blend of the learning process and the gaming experience.
Keywords: Virtual reality, augmented reality, computer technology, script, multimedia.